First report of Equine Parvovirus-Hepatitis (EqPV-H) in Argentina - Olguin Perglione, Cecilia; Politzki, Romina Paula; Alvarez, Irene; Ruiz, Vanesa (Elsevier, 2024)
The novel Equine Parvovirus-Hepatitis (EqPV-H) was first identified in the serum and liver of a horse that died of equine serum hepatitis, also known as Theiler's disease. Several reports in recent years strongly suggest that EqPV-H is the etiologic agent of Theiler's disease. Brazil is the only South American country where infection with this virus has been reported. This study investigated the presence of EqPV-H DNA in horse serum pools (n=51), commercial horse serum batches (n=5) and individual serum samples from donor horses (n=175) from Argentina. All serum samples were analyzed by quantitative polymerase chain reaction (qPCR) and samples with positive or indeterminate results were further analyzed by NS1 nested-PCR for phylogenetic studies.